Percepción contable sobre Normas Internacionales de Información Financiera en empresas privadas de Paraguay, 2015-2020 (Revista Científica UCOM Scientia, 2025)
The study analyzed the perception of 1 352 accountants in Paraguay about International Financial Reporting Standards (IFRS) in private companies (2015-2020). Although Paraguay did not officially adopt IFRS, we sought to understand the knowledge and opinion of accountants. The results showed that many were unfamiliar with IFRS, due to lack of formal adoption and adequate training. The lack of knowledge was seen as an obstacle to implementing IFRS. The need to provide training and resources to improve the understanding and application of these standards was highlighted. Lack of knowledge about IFRS would affect the quality and transparency of financial information with implications for investor decisions and the comparability of financial information globally.